2021
DOI: 10.3389/fimmu.2021.679509
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Lung Resident Group 2 Innate Lymphoid Cells Link Allergic Lung Inflammation and Liver Immunity

Abstract: Group 2 innate lymphoid cells (ILC2s) are tissue resident in the lung and activated by inhaled allergens via epithelial-derived alarmins including IL-33. Activated ILC2s proliferate, produce IL-5 and IL-13, and induce eosinophilic inflammation. Here, we report that intranasal IL-33 or the protease allergen papain administration resulted in increased numbers of ILC2s not only in the lung but also in peripheral blood and liver. Analyses of IL-33 treated parabiosis mice showed that the increase in lung ILC2s was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…Moro et al also reported local expansion of tissue resident ILC2s in fat-associated lymphoid clusters (FALC), lung and bronchoalveolar lavage fluid (BALF) during respiratory inflammation induced by intratracheal IL-33 administration into parabiotic mice (4). Many other groups also used parabiosis models and confirmed ILC2 tissue residency at homeostasis and during inflammation (5)(6)(7)(8).…”
Section: Introduction -Tissue Residency Of Ilc2smentioning
confidence: 93%
See 1 more Smart Citation
“…Moro et al also reported local expansion of tissue resident ILC2s in fat-associated lymphoid clusters (FALC), lung and bronchoalveolar lavage fluid (BALF) during respiratory inflammation induced by intratracheal IL-33 administration into parabiotic mice (4). Many other groups also used parabiosis models and confirmed ILC2 tissue residency at homeostasis and during inflammation (5)(6)(7)(8).…”
Section: Introduction -Tissue Residency Of Ilc2smentioning
confidence: 93%
“…In the human system, helper ILCs, including ILC2s, are underrepresented in the non-mucosal compared to the mucosal tissues due to the abundance of NK cells, similar to mice (19). However, ILC2s are relatively rare in human SI (20), whereas they are one of the major ILC populations in mouse SI (8,21).…”
Section: Tissue Seeding and Adaptation To The Tissue Environmentmentioning
confidence: 99%
“…Tissue-resident ILC2s in the lung are activated by inhaled allergens via epithelial-derived IL-33. Furthermore, intranasal IL-33 administration increased the numbers of ILC2s in the lung, also in peripheral blood and in the liver [ 74 ].…”
Section: Immunological Decision-making I: How Do the Different Damp M...mentioning
confidence: 99%
“…Tissue resident ILC act as local gatekeepers to maintain immunological balance and tissue homeostasis. Although tissue compartmentalization occurs at steady state [ 59 , 60 , 61 , 62 , 63 ], non-NK cell ILC are able to traffic between organs in a tissue and subset-dependent manner upon inflammatory perturbations [ 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. This ability of ILC to migrate to other organs ensures that appropriate immune cells are distributed properly to constrain insults and tissue damage within the body.…”
Section: In Situ Ilc-poiesis and Interorgan Ilc Migrationmentioning
confidence: 99%
“…Early post-infection blood ILC2 were mainly derived from the small intestine and these cells were progressively replaced by lung-derived ILC2 during the course of infection. In addition, intranasal administrations of IL-33 or papain promoted ILC2 migration through the blood stream to the liver [ 70 ]. These findings indicate that local tissue perturbations induce systemic ILC2 migration and type 2 inflammation.…”
Section: In Situ Ilc-poiesis and Interorgan Ilc Migrationmentioning
confidence: 99%